BdFAR4, a root‐specific fatty acyl‐coenzyme A reductase, is involved in fatty alcohol synthesis of root suberin polyester in Brachypodium distachyon. (24th April 2021) - Wang, Yong; Xu, Jiajing; He, Zhaofeng; Hu, Ning; Luo, Wenqiao; Liu, Xiaoyu; Shi, Xue; Liu, Tianxiang; Jiang, Qinqin; An, Peipei; Liu, Le; Sun, Yulin; et al.
SUMMARY: Suberin is a complex hydrophobic polymer of aliphatic and phenolic compounds which controls the movement of gases, water, and solutes and protects plants from environmental stresses and pathogenic infection. The synthesis and regulatory pathways of suberin remain unknown in Brachypodium distachyon . Here we describe the identification of a B. distachyon gene, BdFAR4, encoding a fatty acyl‐coenzyme A reductase (FAR) by a reverse genetic approach, and investigate the molecular relevance of BdFAR4 in the root suberin synthesis of B. distachyon . BdFAR4 is specifically expressed throughout root development. Heterologous expression of BdFAR4 in yeast ( Saccharomyces cerevisiae ) afforded the production of C20:0 and C22:0 fatty alcohols. The loss‐of‐function knockout of BdFAR4 by CRISPR/Cas9‐mediated gene editing significantly reduced the content of C20:0 and C22:0 fatty alcohols associated with root suberin. In contrast, overexpression of BdFAR4 in B. distachyon and tomato ( Solanum lycopersicum ) resulted in the accumulation of root suberin‐associated C20:0 and C22:0 fatty alcohols, suggesting that BdFAR4 preferentially accepts C20:0 and C22:0 fatty acyl‐CoAs as substrates. The BdFAR4 protein was localized to the endoplasmic reticulum in Arabidopsis thaliana protoplasts and Nicotiana benthamiana leaf epidermal cells. BdFAR4 transcript levels can be increased by abiotic stresses and abscisic acid treatment. Furthermore, yeast one‐hybrid, dual‐luciferase activity, and electrophoretic mobility shift assays indicated that the R2R3‐MYB transcription factor BdMYB41 directly binds to the promoter of BdFAR4 . Taken together, these results imply that BdFAR4 is essential for the production of root suberin‐associated fatty alcohols, especially under stress conditions, and that its activity is transcriptionally regulated by the BdMYB41 transcription factor. Significance Statement: We identified and functionally characterized the endoplasmic reticulum‐localized enzyme BdFAR4, which preferentially catalyzes the synthesis of C20:0 and C22:0 fatty alcohols of root suberin in Brachypodium distachyon and is regulated by the R2R3‐MYB transcription factor BdMYB41. Transgenic expression of BdFAR4 afforded production of suberin‐associated fatty alcohols in tomato ( Solanum lycopersicum ) roots, suggesting that BdFAR4 may play an important role in molecular breeding and transgenic strategies to improve suberin production and further enhance drought tolerance of crops.